LEGAL PROTECTION FOR VICTIMS OF SEXUAL VIOLENCE OF MINORS IN WARU ROYOM VILLAGE, DEPOK DISTRICT, CIREBON REGENCY - Rista Tiara Maharani; Moh. Sigit Gunawan (Fakultas Hukum Universitas Swadaya Gunung Jati, 2027)
Background. The increasing incidence of sexual violence against minors highlights persistent challenges in ensuring effective legal protection for child victims despite Indonesia's comprehensive legal framework. Aims. This study examines the implementation of legal protection for child victims of sexual violence in Waru Royom Village, Depok District, Cirebon Regency, identifies the factors influencing its effectiveness, and proposes measures to strengthen victim protection. Methods. An empirical juridical approach was employed, combining statutory, case, and sociological analyses. Primary data were collected through interviews with village officials, police investigators, victim-support institutions, and community representatives, while secondary data were obtained from relevant legislation and scholarly literature. Result. The findings reveal that legal protection has been initiated through victim assistance, family support, institutional coordination, and legal proceedings. However, its effectiveness remains limited due to weak inter-agency coordination, the failure to apprehend the alleged perpetrator, inadequate psychological rehabilitation services, and insufficient integration of victim protection mechanisms at the village level. These shortcomings create a significant gap between the legal guarantees provided by Law No. 35 of 2014 on Child Protection and Law No. 12 of 2022 on Sexual Violence Crimes and their practical implementation. Conclusion. The study concludes that effective protection requires not only comprehensive legislation but also stronger law enforcement, integrated victim recovery services, enhanced institutional capacity at the local level, and sustained collaboration among government agencies, law enforcement authorities, child protection institutions, and the community. Implementation. The study contributes to the literature by demonstrating that the principal challenge in protecting child victims lies not in the absence of legal norms but in the ineffective implementation of existing legal provisions.